Buccal Silicone Granuloma Caused by the Dental Infection - Kazuhiro Murakami; Kazuhiko Yamamoto; Tsutomu Sugiura; Tadaaki Kirita (Hindawi Limited, 2020)
The facial injection of liquid silicone is performed for cosmetic purposes. The use of injectable fillers in facial procedures has become extremely popular over the past decade. Most procedures are performed in the perioral, periocular, and cheek areas of middle-aged women. Even though silicone is biologically inert, its injection can result in the formation of granulomas. Silicone granulomas can result from an inflammatory or autoimmune tissue response. However, the development of silicone granulomas secondary to dental infection has not yet been reported. We report a case of a 73-year-old woman with a right buccal silicone granuloma that developed following a dental infection. Ultimately, this case healed completely after the surgical removal of all lesions. Silicone in the facial region may become infected by a dental infection, and infective silicone develops granulomas and cellulitis. In the context of cosmetic facial silicone injections, it is necessary to improve oral hygiene prior to dental treatment and to maintain a healthy oral environment after surgery. In some cases, surgical treatment using an intraoral approach is effective.